2018
DOI: 10.1158/0008-5472.can-17-2341
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Receptor LRH-1 Functions to Promote Castration-Resistant Growth of Prostate Cancer via Its Promotion of Intratumoral Androgen Biosynthesis

Abstract: Targeting of steroidogenic enzymes (e.g., abiraterone acetate targeting CYP17A1) has been developed as a novel therapeutic strategy against metastatic castration-resistant prostate cancer (CRPC). However, resistance to steroidal inhibitors inevitably develops in patients, the mechanisms of which remain largely unknown. Liver receptor homolog-1 (LRH-1, ) is a nuclear receptor, originally characterized as an important regulator of some liver-specific metabolic genes. Here, we report that LRH-1, which exhibited a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 54 publications
1
37
1
Order By: Relevance
“…PC-3-HNF4α, PC-3-shHNF4α and their empty vectortransduced cells were evaluated of their in vivo tumorigenicity in intact male SCID mice following procedures as described previously [58]. The VCaP-CRPC tumor xenograft model of CRPC was generated as described previously [65,66]. All animal protocols were approved by the CUHK-Animal Experimentation Ethics Committee.…”
Section: Xenograft Tumorigenicity Assaymentioning
confidence: 99%
“…PC-3-HNF4α, PC-3-shHNF4α and their empty vectortransduced cells were evaluated of their in vivo tumorigenicity in intact male SCID mice following procedures as described previously [58]. The VCaP-CRPC tumor xenograft model of CRPC was generated as described previously [65,66]. All animal protocols were approved by the CUHK-Animal Experimentation Ethics Committee.…”
Section: Xenograft Tumorigenicity Assaymentioning
confidence: 99%
“…Recently, Xiao et al. [97] found that liver receptor homolog-1 (LRH-1), a nuclear receptor originally characterized as an important regulator of some liver-specific metabolic genes, had a high expression level in CRPC xenograft models. It can promote de novo androgen biosynthesis by its direct transactivation of several key steroidogenic enzyme genes, elevating intratumoral androgen levels and reactivating AR signaling in abiraterone-treated CRPC tumors.…”
Section: Therapeutic Resistance In Crpcmentioning
confidence: 99%
“…Only recently, in vitro application of SR1848 contributed to the discovery that LRH-1 is also implicated and a possible therapeutic target in castration-resistant prostate cancer (CRPC). 164 This type of cancer is typically associated with persistent androgen receptor (AR) signaling caused by the constant biosynthesis of intratumoral androgens and thus commonly treated with steroidal inhibitors. 165 Xiao et al were able to show that LRH-1 is not only upregulated in CRPC tissue, but also promoting growth and androgen production of prostate cancer cells in vivo.…”
Section: Potential Of Lrh-1 Targeting Approaches In Cancer Therapymentioning
confidence: 99%